Oxidative Stability and Quality Parameters of Veal During Ageing - Mateja Lušnic Polak; Mojca Kuhar; Iva Zahija; Lea Demšar; Tomaž Polak (Polish Journal of Food and Nutrition Sciences)
The objective of the present study was to evaluate the effects of the ageing period (1, 7, 14, and 21 days) on the quality parameters, sensory attributes, and oxidative stability of loins (longissimuss lumborum muscle) obtained from twelve Simmental calves less than 8 months old and slaughtered in a commercial processing plant. After 21 days, the colour of veal samples became yellower (increase in b* colour parameter value), and the instrumentally-measured texture improved (Warner-Bratzler shear force decreased from 84.61 N to 56.79 N). Ageing time enhanced sensory-evaluated tenderness, juiciness, aroma, and flavour. The amount of the lipid oxidation product determined as thiobarbituric acid reactive substance content remained unchanged; in contrast, the amount of protein carbonyls increased, without compromising veal quality.